Identification of Attribution of Runoff Variations in the Tumen River Basin Based on Budyko’s Hypothesis - Dongqing Huo; Jiaqi Wu; Chunzi Zhao; Yongtao Yan; Weihong Zhu; Ri Jin; Jingya Zhou (Hydrology)
The Tumen River Basin (TRB), a critical China border region, has experienced a complex evolution of runoff due to climate change and human activities. This study aims to quantify the main drivers of runoff variations in the TRB based on the Budyko framework to assess the relative contributions of climate change and human activities to runoff fluctuations. Results indicate pronounced warming and increased precipitation in the TRB, while runoff exhibits a declining trend with temporal variability. Runoff decreased during 1956–1980 but increased post 1980. Overall, climate change is the dominant factor driving runoff fluctuations in the TRB. A comparison across different sub-basins shows that the contribution of climate change to runoff variations is higher in the middle and upper reaches of the Tumen River, reaching up to 93.8%. In the lower basin, human activities contribute significantly to runoff variations. Higher forest cover and reservoir construction help maintain the long-term stability of watershed runoff. This study provides a scientific basis and data support for water resources development and ecological protection in the basin.